Training volume and personal best time in marathon, not anthropometric parameters, are associated with performance in male 100-KM ultrarunners - Knechtle, B.; Wirth, A.; Knechtle, P.; Rosemann, T. (The Journal of Strength and Conditioning Research, 2010)
We investigated the relation between selected anthropometric and training variables and the personal best time in a marathon with total race time in 66 Caucasian male nonprofessional ultrarunners in a 100-km run. In the multiple linear regression analysis, the average weekly training volume in kilometers (r2 = 0.224, p < 0.01) and the personal best time in a marathon (r2 = 0.334, p < 0.01) were significantly associated with total race time, whereas no anthropometric variable was related to race performance (p > 0.05). We conclude that high training volume and a fast time in a marathon were more important for a fast race time in male 100-km runners than any of the determined anthropometric variables.